Towering judges : a comparative study of constitutional judges / edited by Rehan Abeyratne, The Chinese University of Hong Kong, Iddo Porat, College of Law and Business, Israel. - Abeyratne, Rehan; Porat, Iddo (Comparative constitutional law and policy., 2021)
In Towering Judges: A Comparative Study of Constitutional Judges, Rehan Abeyratne and Iddo Porat lead an exploration of a new topic in comparative constitutional law: towering judges. The volume examines the work of nineteen judges from fourteen jurisdictions, each of whom stood out individually among their fellow judges and had a unique impact on the trajectory of constitutional law. The chapters ask: what makes a towering judge; what are the background conditions that foster or deter the rise of towering judges; are towering judges, on balance, positive or detrimental for constitutional systems; how do towering judges differ from one jurisdiction to another; how do political and historical developments relate to this phenomenon; and how does all of this fit within global constitutionalism? The answers to these questions offer important insight into how these judges were able to shine to an uncommon degree in a profession where individualism is not always looked on favourably.